2019
DOI: 10.1016/j.redox.2019.101155
|View full text |Cite
|
Sign up to set email alerts
|

Age-related loss of mitochondrial glutathione exacerbates menadione-induced inhibition of Complex I

Abstract: The role of mitochondrial GSH (mGSH) in the enhanced age-related susceptibility to xenobiotic toxicity is not well defined. We determined mGSH status and indices of mitochondrial bioenergetics in hepatocytes from young and old F344 rats treated with 300 μM menadione, a concentration that causes 50% cell death in old. At this concentration, mGSH was significantly lost only in hepatocytes from old rats, and with near total depletion due to lower basal mGSH in aged cells. In old hepatocytes, menadione caused mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…GSH is also a redox regulator of electron transport chain (ETC) proteins that perform oxidative phosphorylation, a process involving the sequential transfer of electrons between the five ETC protein complexes embedded in the inner mitochondrial membrane (IMM) [ 78 , 79 ]. Regulation of these ETC proteins suggest a possible link between mitochondrial metabolism and redox homeostasis through mGSH status [ 80 ]. mGSH depletion significantly decreased mitochondrial basal respiration and ATP production, and the reserve capacity in human RPE cells suggests an oxidative stress-dependent mechanism [ 81 ].…”
Section: Mitochondrial Gsh and Its Critical Rolementioning
confidence: 99%
See 1 more Smart Citation
“…GSH is also a redox regulator of electron transport chain (ETC) proteins that perform oxidative phosphorylation, a process involving the sequential transfer of electrons between the five ETC protein complexes embedded in the inner mitochondrial membrane (IMM) [ 78 , 79 ]. Regulation of these ETC proteins suggest a possible link between mitochondrial metabolism and redox homeostasis through mGSH status [ 80 ]. mGSH depletion significantly decreased mitochondrial basal respiration and ATP production, and the reserve capacity in human RPE cells suggests an oxidative stress-dependent mechanism [ 81 ].…”
Section: Mitochondrial Gsh and Its Critical Rolementioning
confidence: 99%
“…Treatment of RPE cells with phenyl succinate (PS—an inhibitor of OGC) or butylmalonate (BM—an inhibitor of DIC) caused a disruption of complex II. It has been demonstrated that acute oxidative stress to the mitochondria caused significant vulnerability to complex I in rat hepatocytes [ 80 ]. However, no significant change was noticed in the respiratory chain complex V.…”
Section: Mitochondrial Gsh and Its Critical Rolementioning
confidence: 99%
“…Our results on the expression pattern of complex I have to be interpreted with caution because of the close proximity of complex I and IV bands in WB analysis under non-reducing conditions. It was reported under acute redox cycling challenge to mitochondria that the complex I protein is more vulnerable [59]. However, a complex V segment of the respiratory chain was less impacted.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, mGSH also plays a critical role in supporting redox signaling and the biosynthesis of iron-sulfur (Fe-S) cluster cofactors within the mitochondrial matrix. The regulation of OXPHOS proteins suggests a possible link between mitochondrial metabolism and redox homeostasis, potentially via mGSH status [13].…”
Section: Introductionmentioning
confidence: 99%